2023
DOI: 10.1111/jcmm.17665
|View full text |Cite
|
Sign up to set email alerts
|

Duvelisib attenuates bleomycin‐induced pulmonary fibrosis via inhibiting the PI3K/Akt/mTOR signalling pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Previous animal studies have revealed that PI3K-γ activation induced epithelial-mesenchymal transition and contributed to bleomycin-induced pulmonary fibrosis [33][34][35]. However, a PI3K-γ inhibitor can attenuate bleomycin-induced pulmonary fibrosis [36]. Our recent study demonstrated that the PI3K-γ pathway mediates MV-induced aggravation of epithelial-mesenchymal transition and pulmonary fibrosis after bleomycin-induced ALI [23].…”
Section: Discussionmentioning
confidence: 78%
“…Previous animal studies have revealed that PI3K-γ activation induced epithelial-mesenchymal transition and contributed to bleomycin-induced pulmonary fibrosis [33][34][35]. However, a PI3K-γ inhibitor can attenuate bleomycin-induced pulmonary fibrosis [36]. Our recent study demonstrated that the PI3K-γ pathway mediates MV-induced aggravation of epithelial-mesenchymal transition and pulmonary fibrosis after bleomycin-induced ALI [23].…”
Section: Discussionmentioning
confidence: 78%
“…Previous animal studies have revealed that PI3K-γ activation induced epithelial–mesenchymal transition and contributed to bleomycin-induced pulmonary fibrosis [ 35 , 36 , 37 ]. However, a PI3K-γ inhibitor can attenuate bleomycin-induced pulmonary fibrosis [ 38 ]. Our recent study demonstrated that the PI3K-γ pathway mediates MV-induced aggravation of epithelial–mesenchymal transition and lung fibrosis after bleomycin-induced ALI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fei Qi et al found that lncRNA TUG1 induced autophagy and suppressed inflammation and EMT through inhibition of the PI3K/Akt/mTOR signaling pathway, resulting in an improved pulmonary fibrosis phenotype [33]. Xiaohe Li et al obtained similar outcomes that Duvelisib silenced the expression of fibroblasts in the lungs of patients with IPF and activated autophagy by inhibiting the PI3K/Akt/mTOR signaling pathway [34]. The PI3K-Akt signaling pathway also plays an important role in the progression of cancers.…”
Section: Prediction and Validation Of Candidate Drugsmentioning
confidence: 97%